ONE CGIAR in Rwanda - International Institute of Tropical Agriculture; International Center for Tropical Agriculture; International Potato Center; International Food Policy Research Institute; CGIAR Research Program on Climate Change, Agriculture and Food Security (2022)
CGIAR centers invest in technological and institutional innovations, partnerships, capacity development, and policy engagement to contribute to Rwanda’s agricultural transformation. This brief is a contribution of various One CGIAR centres in Rwanda. The centres are International Institute of Tropical Agriculture (IITA) , International Center for Tropical Agriculture (CIAT) through Pan Africa Bean Research Alliance, International Potato Center (CIP), International Food Policy Research Institute (IFPRI), CGIAR Research Program on Climate Change, Agriculture, and Food Security (CCAFS)